The Relationship Between Flight Hours Duration And Menstruation Disturbances In Flight Attendant - Nurwiliani, Lia; Nuromah, Norma; Chotimah, Ratih Ayu Chusnul (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
A Flight attendant has a higher risk of menstrual disturbances than a non-flight crew. Moreover, a flight attendant has high work pressure with flight duration of 225 hours (3 months) which will cause work stress and menstrual disturbance. The purpose of this study was to find out the relationship between flight hours and menstrual disturbances in flight attendants. This research method is quantitative study with a cross-sectional approach and was carried out to 51 respondents. The sampling technique used was total sampling, while the data collection used interview guidelines. In addition, the data analysis used Chi-Square. The results of the study were based on the Chi-Square test of flight attendants with flying hours 225 hours in the last 3 months. There were28 respondents (96.6%) who experienced menstrual disturbances, while there was 1 respondent (3.4%) who did not experience menstrual disturbances. The obtained P value was 0.000 which meant the P value was < 0.05, while the Odd Ratio (OR) was 40,444, so it can be concluded that there was a significant relationship between flight hour duration and menstrual disturbances among the flight attendants at Mess Kanya Sena 2, Jakarta